Translational stalling at polyproline stretches is modulated by the sequence context upstream of the stall site. Issue 16 (20th August 2014) - Starosta, Agata L.; Lassak, Jürgen; Peil, Lauri; Atkinson, Gemma C.; Virumäe, Kai; Tenson, Tanel; Remme, Jaanus; Jung, Kirsten; Wilson, Daniel N.
Abstract: The polymerization of amino acids into proteins occurs on ribosomes, with the rate influenced by the amino acids being polymerized. The imino acid proline is a poor donor and acceptor for peptide-bond formation, such that translational stalling occurs when three or more consecutive prolines (PPP) are encountered by the ribosome. In bacteria, stalling at PPP motifs is rescued by the elongation factor P (EF-P). Using SILAC mass spectrometry of Escherichia coli strains, we identified a subset of PPP-containing proteins for which the expression patterns remained unchanged or even appeared up-regulated in the absence of EF-P. Subsequent analysis using in vitro and in vivo reporter assays revealed that stalling at PPP motifs is influenced by the sequence context upstream of the stall site. Specifically, the presence of amino acids such as Cys and Thr preceding the stall site suppressed stalling at PPP motifs, whereas amino acids like Arg and His promoted stalling. In addition to providing fundamental insight into the mechanism of peptide-bond formation, our findings suggest how the sequence context of polyproline-containing proteins can be modulated to maximize the efficiency and yield of protein production.